ENERGY CHARACTERISTICS OF SOLAR PHOTOELECTRIC INSTALLATIONS UNDER THE COMBINED PRODUCTION OF HEAT AND ELECTRIC ENERGY IN THE CONDITIONS OF UZBEKISTAN - Otamirzaev, D.R. (International Journal of Psychosocial Rehabilitation, 2020)
The possibility of increasing the total conversion coefficient of solar installations by generating heat and electricity from one receiving surface is being considered. To achieve this goal, a thermophotoelectric installation is proposed that combines a photoelectric module and a thermal collector. For experiments, the installation was used: combined thermophotoelectric conversion of solar energy. The results of comparative experimental studies of the proposed facilities are presented.